An Energy Evaluation in a Vapor Compression Refrigeration System Utilizing R32 Refrigerant - Hasanudin Hasanudin; Ananda Duta Suhendar; Amri Abdulah; Renata Lintang Azizah; Khoirudin; Karyadi; Murtalim; Abduh Al Afgani (Mechanical Engineering Department Universitas Buana Perjuangan Karawang, 2023)
This article reports the results of a study into the efficiency of refrigeration systems. The efficiency of the refrigerant-based cooling system is a significant issue due to its connection to global warming. Vapour compression refrigeration (VCR) systems utilise the inverted Rankine cycle to provide cooling process. Existing systems are evaluated and controlled, and their efficacy is either maintained or improved. A VCR device explores evaporator load variations at five different rpm levels as test equipment for measuring the performance coefficient of R32 refrigerant. A 365-watt compressor drives the VCR system. R32 is a more eco-friendly alternative to R22 as a refrigerant. Interpolation and extrapolation were utilized and adapted to convert the system's experimental enthalpy value to total performance. Genetron was chosen to evaluate enthalpy alongside other factors, such as VCR performance. Genetron properties was used to double-check the experiment's findings. The highest CoP was found and evaluated at a speed of 400 rpm (1st level) with the result about 3.17. The lowest value for CoP was found and achieved at the maximum attainable rpm, which was 2.53. The association between CoP and fan speed is inversely proportional during evaporator loading. Genetron properties software validation results produced an average CoP value of less than 10% compared to experimental data. In addition, this work significantly contributes to the study of VCR performance through the development of test devices for the provided VCR system